Online Teaching Effectiveness: A Tale of Two Instructors - Gorsky, Paul; Blau, Ina (International Review of Research in Open and Distributed Learning, 2009)
Upon completion of a graduate level course at the Open University of Israel, one instructor received very high student ratings while the other received very low ratings. We utilized this exceptional situation to perform ad hoc analyses of their course forums. The objective of this study was to map the dialogic behavior that occurred and to create suggestions for best practice and for worst practice in terms of active and passive participation, instructor response time, and the extent of teaching presence, social presence, and cognitive presence.